SISTEM GARANSI BARANG ELEKTRONIK DALAM FIQIH MUAMALAH DAN UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Syahrizal Abbas; Edi Yuhermansyah; Dara Masyittah (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2019)
In a transaction, especially elecronic goods can not be separated from the possibility of defects or damage to goods traded in the future, causing electronic goods manufacturers to provide guarantess ( warranty ) and impose and right to consumers with certain conditions. Regarding the time or warranty period for an item according to Malikiyah scholars whose nature is not perishable takes longer. In general, currently electronic goods are only given a one-year warranty period. Whereas in Law Number 8 Article 27 of 1999 concerning the Consumer Protection Law, the risk period for goods traded within a period of 4 years has been contained. The formulation of the problem and the pupose of this study is to find out how the warranty system is in muamalah fiqh and how is the guarantee system in the consumer protection law. The research method used can be classified as a descriptive analysis of reseach in two perspectives, namely in muamalah fiqh and UUPK, and with a qualitative approach, data is obtained through library research. The resulth of this study show that the warranty system in muamalah fiqh shows that the khiyar system for goods that have defects or damage in them ( disgrace ) applies when there is a defect ( disgrace ) damage to goods that are not easily damaged. Regarding the time to sue for losses is not set a definite time limit because items that are not easily damaged, especially electronics require a long time. And the results of research into the warranty system in the UUPK stipulate that the seller or business actor is obliged to provide guarantess for goods sold as a form of warranty for damaged goods, and the seller will be subject to criminal sanctions when compensation claims made by the consumer are rejected or not fulfilled. Regarding the time limit for the prosecution of damaged goods is set for 4 ( four ) years.